A multivariate approach to study the maintenance of soil fertility and soil health in relation to yield and nutrition of rice (Oryza sativa) - Mandal, Mitali; Panda, Narayan; Patra, Prasanta Kumar (ORYZA-An International Journal of Rice, 2021)
Understanding the relationship between soil properties and grain yield and yield related traits is an importantÂ objective in crop production programme. The purpose of this study was to evaluate maintenance of soil healthÂ in terms of soil chemical properties in relation to rice yield using multivariate analytical methods. CanonicalÂ correlation analysis is one of the most popular multivariate analysis techniques to estimate dependentÂ relationship between soil properties with grain yield and yield attributing characters .In this study, five canonicalÂ correlation coefficients ( CCCs) were estimated and the first three of them were significant( R1: 1, R2: 0.99 andÂ R3: 0.84, p<0.001).The findings obtained from the CCA indicate that available N, available Cu and Zn in soilÂ and N content in grain had the largest contribution for the explanatory capacity of canonical variablesÂ estimated from grain yield, straw yield, number of panicles/m2 and filled grains / panicle.